Irrigation control by mimicry. Issue 32 (2022) - Manzano, J.M.; Bareiro, J.; Cáceres, G.B.; Salvador, J.R.; Millán, P.
Abstract: In this paper, an automatic control is designed to mimic the irrigation commands of the farmer. It is aimed to avoid manual operation over vast fields. In addition, the structure required for its deployment is analysed in detail, both off-field and of-field. A cloud computing environment has been built, which monitorizes variables of the farm while computing the control actions to be fed to solenoid valves. The proposal has been deployed in a bell pepper field in Paraguay. The results show its effectiveness in remotely and automatically following the references applied.